NEGATIVE POLITENESS STRATEGY IN A STAND-UP COMEDY - Kholis, Firman Maulana; Sugaryamah, Deuis; Listiani, Toneng (Universitas Islam Negeri Sunan Gunung Djati, 2024)
The aim of this study was to identify the factors influencing Trevor Noah’s use of negative politeness strategies in his stand-up comedy special “Atlanta Afraid of the Dark” (2016). Employing a qualitative descriptive approach, the research examined and explained the types and influencing factors of negative politeness strategies in Noah’s performance. The study utilized Brown and Levinson’s theories on politeness strategies, particularly negative politeness, to identify and categorize these strategies and their influencing factors. Additionally, Ramon Papana’s framework for the structural build of stand-up comedy techniques was used to analyze the elements of Noah’s comedy. The study found that Noah frequently used impersonal humor in his jokes. It also revealed that social context significantly impacted the content of the jokes, with Noah purposefully addressing social issues. The findings showed that Noah’s humor often employed negative politeness techniques, such as being indirect, questioning, hedging, and depersonalizing both the speaker and the listener. In conclusion, the negative politeness strategies of pessimism, questioning, hedging, and depersonalization played a crucial role in delivering the punchlines. Additionally, callbacks were created using negative politeness methods, such as showing deference and apologizing.Keyword: comedy, politeness strategy, negative politeness strategy